Perlindungan Anak dari Grooming Seksual Dalam Perspektif Hukum Islam Dan Hukum Positif: Kajian Yuridis-Normatif Komparatif - Abdul Basit; Ridwan Bahrudin; Muhamad Noval Arahman (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Child sexual grooming has become an alarming form of violence in the digital era, as offenders exploit online media to approach, manipulate, and exploit children. This article aims to analyze child sexual grooming from the perspectives of positive law and Islamic law. The study employs a normative juridical method with a qualitative approach, conducted through library research with descriptive-analytical and comparative analysis. The findings reveal that Indonesian positive law, particularly the Child Protection Law and the Sexual Violence Crime Law, criminalizes grooming, yet legal gaps remain, especially in addressing digital-based crimes. In Islamic law, grooming is classified as jarīmah and jināyah because it violates the principles of maqāṣid al-sharī‘ah, which emphasize the protection of religion, life, intellect, honor, and property. The comparative analysis demonstrates that integrating Islamic legal values with positive law could strengthen child protection mechanisms and provide a more comprehensive normative foundation. Therefore, enhancing regulations through the synergy of both legal systems is crucial in preventing and addressing cases of child sexual grooming.